The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2337/dc12-2617
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Dose Prednisolone on Hepatic and Peripheral Insulin Sensitivity, Insulin Secretion, and Abdominal Adiposity in Patients With Inflammatory Rheumatologic Disease

Abstract: OBJECTIVEThe metabolic effects of low-dose prednisolone and optimal management of glucocorticoid-induced diabetes are poorly characterized. The aims were to investigate the acute effects of low-dose prednisolone on carbohydrate metabolism and whether long-term low-dose prednisolone administration increases visceral adiposity, amplifying metabolic perturbations.RESEARCH DESIGN AND METHODSSubjects with inflammatory rheumatologic disease without diabetes mellitus were recruited. Nine subjects (age, 59 ± 11 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 40 publications
(53 reference statements)
3
49
1
Order By: Relevance
“…However, in contrast to the above-mentioned inhibitory effects observed in both acute and long-term GC incubation, chronic in vivo administration of these steroids leads to up-regulation of b-cell function as a result of the compensatory adaptation to GC-induced IR. Administration of high doses of prednisolone (30 mg) or dexamethasone (2-15 mg) to healthy individuals for prolonged periods (up to 15 days and up to 4 days respectively) resulted in normoglycaemia or a modest increase in fasting glycaemia (Beard et al 1984, Schneiter & Tappy 1998, Hollindgal et al 2002, Willi et al 2002, Nicod et al 2003, Ahrén 2008, van Raalte et al 2010, Petersons et al 2013. Importantly, in most of these studies, volunteers developed hyperinsulinaemia.…”
Section: Chronic Effects Of Gcsmentioning
confidence: 99%
“…However, in contrast to the above-mentioned inhibitory effects observed in both acute and long-term GC incubation, chronic in vivo administration of these steroids leads to up-regulation of b-cell function as a result of the compensatory adaptation to GC-induced IR. Administration of high doses of prednisolone (30 mg) or dexamethasone (2-15 mg) to healthy individuals for prolonged periods (up to 15 days and up to 4 days respectively) resulted in normoglycaemia or a modest increase in fasting glycaemia (Beard et al 1984, Schneiter & Tappy 1998, Hollindgal et al 2002, Willi et al 2002, Nicod et al 2003, Ahrén 2008, van Raalte et al 2010, Petersons et al 2013. Importantly, in most of these studies, volunteers developed hyperinsulinaemia.…”
Section: Chronic Effects Of Gcsmentioning
confidence: 99%
“…Excess GCs in circulation, such as occurs during Cushing disease or chronic GC therapy, promote both visceral fat deposition and hepatic insulin resistance (45,46). An increase in hepatic insulin resistance contributes to hyperglycemia in mouse models and in human subjects (47,48).…”
Section: Ms4 Does Not Promote Adipogenesis or Gluconeogenic Gene Exprmentioning
confidence: 99%
“…GCs are known to increase insulin resistance by facilitating hepatic glucose production and reducing peripheral glucose disposal (14)(15)(16). As a result, the use of GCs is associated with a risk of development or worsening of glucose intolerance, which is well known as one of the major adverse effects of GC therapy (17).…”
mentioning
confidence: 99%
“…hepatic glucose production and reducing peripheral glucose disposal (14)(15)(16). In healthy humans, it has been reported that insulin secretion is two-to fourfold increased to compensate increased insulin resistance after short-term GC administration (21)(22)(23).…”
mentioning
confidence: 99%